Attributes of female directors and accruals-based earnings management - Hany Elzahar; Alaa Zalata; Marwa Hassaan (Cogent Business & Management, 2022)
Based on the notion that female directors are superior in monitoring and informed by a theoretical framework that draws insights from agency, resource dependence, and upper echelon theories, this study investigates the impact of female monitoring director's tenure and busyness on mitigating managerial opportunistic behavior, applying to a sample of US firms over the period from 1998 to 2014. In line with the theoretical foundation, results demonstrate that both long tenure and more directorships have a positive impact on female directors monitoring competency. This finding is auxiliary supported by the further analysis considering the impact of the Sarbanes-Oxley act on the association between monitoring female directors' attributes and earnings management practices. Accordingly, this study contributes to the literature on the influence of different attributes of female monitoring directors on their monitoring competency. This in turn provides an insight to decision makers that could help in recruitment of female directors that can better enhance monitoring effectiveness of corporate boards.
Keywords: 650; agency theory; earnings management; Monitoring female directors; resource dependence theory; SOX; upper echelon theory